Is it possible to automate the discovery of process maps for the time-driven activity-based costing method? A systematic review - Franciele Iachecen; Marcelo Rosano Dallagassa; Eduardo Alves Portela Santos; Deborah Ribeiro Carvalho; Sérgio Ossamu Ioshii (BMC, 2023)
Abstract Objectives The main objective of this manuscript was to identify the methods used to create process maps for care pathways that utilized the time-driven activity-based costing method. Methods This is a systematic mapping review. Searches were performed in the Embase, PubMed, CINAHL, Scopus, and Web of Science electronic literature databases from 2004 to September 25, 2022. The included studies reported practical cases from healthcare institutions in all medical fields as long as the time-driven activity-based costing method was employed. We used the time-driven activity-based costing method and analyzed the created process maps and a qualitative approach to identify the main fields. Results A total of 412 studies were retrieved, and 70 articles were included. Most of the articles are related to the fields of orthopedics and childbirth-related to hospital surgical procedures. We also identified various studies in the field of oncology and telemedicine services. The main methods for creating the process maps were direct observational practices, complemented by the involvement of multidisciplinary teams through surveys and interviews. Only 33% of the studies used hospital documents or healthcare data records to integrate with the process maps, and in 67% of the studies, the created maps were not validated by specialists. Conclusions The application of process mining techniques effectively automates models generated through clinical pathways. They are applied to the time-driven activity-based costing method, making the process more agile and contributing to the visualization of high degrees of variations encountered in processes, thereby making it possible to enhance and achieve continual improvements in processes.